2007
DOI: 10.1189/jlb.1106683
|View full text |Cite
|
Sign up to set email alerts
|

A 5.8-kDa component of manuka honey stimulates immune cells via TLR4

Abstract: Honey is used as a therapy to aid wound healing. Previous data indicate that honey can stimulate cytokine production from human monocytes. The present study further examines this phenomenon in manuka honey. As inflammatory cytokine production in innate immune cells is classically mediated by pattern recognition receptors in response to microorganisms, bacterial contamination of honey and the effect of blocking TLR2 and -4 on stimulatory activity were assessed. No vegetative bacteria were isolated from honey; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(124 citation statements)
references
References 46 publications
1
119
1
3
Order By: Relevance
“…An acidic environment, antioxidant effects, antiinflammatory effects, antibacterial properties and immunemodulator effects enable more rapid and adequate wound healing (7). Tonks et al found in their study that the 5.8 kDa component of MH stimulates the TNF α production in macrophages through the toll-like receptor (21,22,23). It was…”
Section: Discussionmentioning
confidence: 96%
“…An acidic environment, antioxidant effects, antiinflammatory effects, antibacterial properties and immunemodulator effects enable more rapid and adequate wound healing (7). Tonks et al found in their study that the 5.8 kDa component of MH stimulates the TNF α production in macrophages through the toll-like receptor (21,22,23). It was…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that Manuka honey increased IL-1beta, IL-6, and TNF-alpha production from Mono Mac6 cells or human monocytes [71,72], and the active component was 5.8 kDa, which increased production of these cytokines via TLR4 [73]. In addition, it was reported that oral intake of honey augmented antibody productions in primary and secondary immune responses against thymus-dependent and thymusindependent antigens [74].…”
Section: Immune Functionmentioning
confidence: 96%
“…Calendula has various anti-bacterial and anti-fungal activities (Rossiter et al, 2006;Tonks et al, 2007) and has been used for the treatment of abrasions, burns, ulcers, skin inflammations, eczema and wounds (Schulz et al, 2004). CO flower extract has an antibacterial activity against various bacteria.…”
Section: Anti-bacterial and Antifungal Activitymentioning
confidence: 99%